The nature of chronic and transient poverty: analyzing poverty dynamics in Nepal - Khanal, Prabin (Economic Journal of Development Issues, 2015)
Cross sectional data are widely applied for studying and analyzing poverty at a particular point in time. However, it does not incorporate the changes in welfare level of an individual over a period in time. This paper uses the concept of poverty dynamics for studying the chronic and transient nature of poverty in different areas of Nepal. Using the data of Nepal Living Standard Survey (NLSS) of 1995/96 and 2003/04, this study reveals that the concentration of chronic poverty is larger than the transient poverty. Policies required for taking out chronic and transient poor from the state of poverty should be applied in a different way.DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11870Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 102-115